(NpOLIFONIQ(B.(N~ASTX (B1s (NU^EBNIK DLQ MUZYKAL_NYH WUZOW(B.s - (Na(B.(NmILKA(B.s; (Nk(B.(N`VAK(B.s (NNAU^NYJ REDAKTOR(B.s ((NsANKT(B-(NpETERBURGs (NkOMPOZITORs, 2016)
(Nw PREDLAGAEMOM U^EBNIKE WPERWYE POLNOMAS[TABNO PEREDSTAWLENA LELINGRADSKAQ(B-(NPETERBURSKAQ POLIFONI^ESKAQ [KOLA(B.s
(NrOSSISKIJ KNIGA I ON O^EN DOROGO(B.s
Keywords: (NtEORIQ(B.s